THE EFFECTIVENESS OF THE WEBSITE-BASED INQUIRY LEARNING MODEL ASSISTED BY VIDEO MEDIA IN ELEMENTARY SCHOOLS - Nilna Mayang Kencana Sirait; MZ Muttaqien H. Lagala; Maftuhah Dewi (Adisam Publisher, 2024)
The Inquiry Learning Model has the advantage in its application, namely that meaningful learning occurs. Students who learn to complete an invention will maximize all the knowledge they have and find out what knowledge to use. Learning using the inquiry learning model will have more meaning when teachers are able to expand the level of educator knowledge to the basics of theory and concepts. A media will be tried to be applied in the development of learning media, namely in the form of learning videos presented in Microsoft Powerpoint which aims to make learning more effective, interesting and fun so that it can improve students' learning outcomes and understanding of concepts. The inquiry model-based learning video media that has been developed has a design using the ADDIE development model which includes five stages, namely analysis, design, development, implementation and evaluation. Overall, this model shows great potential in improving students' critical thinking skills and is worthy of consideration for implementation in the basic education curriculum.